(untitled) (International Journal of Innovative Technologies in Economy, 2025)
This study provides a comprehensive analysis of the global tourism services market by clustering countries according to the Tourism Destination Competitiveness Index. The research examines four key indicators - international tourist arrivals, the Network Readiness Index, the Sustainable Development Index, and the Quality of Life Index - which together capture the essential aspects of tourism industry development and allow for an objective assessment of each country’s attractiveness for tourists. Using both hierarchical clustering and k-means clustering methods on the statistical dataset, the study identifies four distinct groups of countries with varying characteristics. A discriminant analysis is additionally employed to quantify the impact of each factor on the probability that a country belongs to a specific cluster. The empirical results highlight the substantial unevenness in the global distribution of tourist flows and the significant disparities in digital infrastructure development, sustainability, and living standards. Notably, the third cluster emerges as the most competitive, comprising countries that combine high volumes of tourist arrivals with advanced infrastructure and robust sustainability standards. Based on these findings, the study underscores the importance of an integrated approach that simultaneously strengthens digital readiness, sustainability, and quality of life to enhance tourism competitiveness in the global market.